An application of choice-based conjoint analysis to measure willingness to pay for casino buffets - Tevfik Demirciftci; Amanda Belarmino; Carola Raab (International Hospitality Review)
Purpose – The purpose of this study is to discover what attributes of casino buffet restaurants are the most important for customers’ willingness to pay (WTP). Design/methodology/approach – Choice-based conjoint analysis was used in this study to test seven attributes: food, price/value, real price, service, atmosphere, the number of reviews and user-generated star ratings. Sawtooth Software was used to do the conjoint analysis, and a series of significance t-tests were run to determine the significance of each attribute on WTP with Statistical Package for the Social Sciences (SPSS). Findings – Based on a survey of 483 respondents who had visited a buffet at a casino within the last two years, this study found that food is ranked as the most significant attribute of a casino buffet restaurant, followed by real price and service quality. Originality/value – Theoretically, this work is the first to the authors’ knowledge to apply the antecedents of behavioral intention to willingness-to-pay for niche restaurants. Practically, the results of this study will help casino buffet operators as they re-open after COVID-19. Future studies could collect data in the post-pandemic environment and examine WTP at casino buffets in different geographic locations.